Spatial orientation in virtual environment compared to real-world. Issue 6 (5th October 2021) - Pastel, S.; Chen, C. H.; Bürger, D.; Naujoks, M.; Martin, L. F.; Petri, K.; Witte, K.
Abstract: Virtual reality (VR) is popular across many disciplines and has been increasingly used in sports as a training tool lately. However, it is not clear whether the spatial orientation of humans works equally within VR and in the real-world. In this paper, two studies are presented, in which natural body movements were allowed and demanded. Firstly, a series of verbal and walking distance estimation tests were conducted in both the virtual and the real environment. The non-parametric Friedman test with pairwise comparisons showed no significant differences neither in verbal nor in walking distance estimations between the conditions (all p > 0.05). However, shorter distances (0.9-1.5 m) were estimated more precisely than larger distances (2.6-2.8 m) in both environments. Secondly, a self-developed route recall test to examine the spatial orientation was performed in the virtual and the real environment. The participants visually perceived the predefined route and were instructed to follow these routes with their eyes blindfolded and afterward to return to their starting position. Between the ending and the starting position, no difference between the two environments was observed (p > 0.05). Based on these two studies, the performance of the human spatial orientation preliminarily verified the same in a virtual and real environment.